Herança dos teores de β-caroteno e sacarose em melão - Silva, Juliana Maria Costa da (Universidade Federal Rural do Semi-Árido, 2017)
Improving the quality of melon is one of the main objectives of a breeding program. Knowledge of trait inheritance assists the researcher in the choice of breeding strategy, giving greater security in the selection process and allowing higher genotypic values to be identified and selected, saving time and resources. The objective of the present work was to study the inheritance of β-carotene content, sucrose content and soluble solids in melon. The F1, F2, RC1, RC2 generations of the Vedrantais x A-16 crossing were evaluated in randomized blocks with three replicates. The A-16 (subsp. melo var. acidulus) strain has a white mesocarp, low levels of β-carotene, sucrose and soluble solids, while the Vedrantais (subsp. melo var. reticulatus) strain has orange mesocarp and high β -carotene, sucrose and soluble solids. Nine loci and a partial dominance were estimated with β-carotene content. Segregations in the F2 and backcross generations indicated that the content of β-carotene in melon is conferred by a major gene with additive and dominance effects associated with polygenes with additive effects. It was verified that the sucrose is the main factor that counts the genetic and environmental variability observed in the sugar content between the parents. In the inheritance of sucrose content, there is a major gene with additive and dominance effects associated with polygenes with additive effects. The inheritance of soluble solids involves a major gene with additive and dominance effects associated with polygenes and the presence of epistasis
Inheritance of β-carotene and sacarose contents in melon
Keywords: Cucumis melo; Melhoramento vegetal; Qualidade; Carotenóides; Hexose; Açúcares; HPLC; Cucumis melo; Vegetable breeding; Quality; Carotenoids; Hexose; Sugars; HPLC; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA